Acute bilateral renal vein thrombosis complicating Netherton syndrome - Pohl, Martin; Zimmerhackl, Lothar Bernd; Haußer-Siller, Ingrid; Ludwig, H.; Hildebrandt, F.; Gordjani, N.; Sutor, Anton H.; Anton-Lamprecht, Ingrun; Brandis, M. (European journal of pediatrics, 1998)
A 1-year old male infant suffering from Netherton syndrome with severe generalized erythroderma presented with acute renal failure due to bilateral renal vein thrombosis (RVT) after a short episode of enteritis. The imperceptible fluid loss through the skin and the additional enteric water loss had led to decompensation of the delicate fluid balance and had resulted in RVT as a sequel of haemoconcentration. Reperfusion of the left kidney could be achieved by treatment with urokinase and heparin. Prophylactic oral anticoagulation was instituted for several weeks.